Adapting Traditional Communication Through Banner Design: The Role of Village Government Media in the Digital Disruption Era - Putra, I Dewa Putu Pasnadi; Widiastini, Ni Made Ary; Heryanda, Komang Krisna (International Journal of Economics Development Research (IJEDR), 2025)
Werdhi Bhuwana Village, located in Mengwi District, Badung Regency, serves as an example of a rural community in Badung that continues to rely on conventional media such as banners and billboards as visual communication tools to disseminate information to its residents. The use of billboards in strategic locations—such as in front of the village office, at major intersections, and in other public spaces—remains common and serves as a primary medium for conveying information about village programs and governmental achievements. This phenomenon indicates that, despite the rapid development and dominance of digital media, printed visual media such as banners have not been entirely replaced. This situation calls for concrete and measurable solutions from the Werdhi Bhuwana Village Government. By implementing the solutions proposed in this study, it is expected that banners will not only persist but also improve in effectiveness and relevance as modern communication tools amidst the current digital disruption. This research employs a descriptive qualitative approach, chosen to provide an in-depth and contextual understanding of the existence and effectiveness of banner (billboard) design utilized by the Werdhi Bhuwana Village Government as an information medium for the community.